Urban mutation in Algeria: the functional evolution of Ali Mendjeli - Saidi, Ikram; Saidi, Feyrouz Ahlam (Human Geography Journal, 2025)
The dominant function of a city plays a crucial role in shaping its identity, influencing how it is perceived and experienced, and ultimately guiding its growth. The new town of Ali Mendjeli, located in northeastern Algeria, was established as a strategic response to Constantine’s urban saturation, housing shortages, and increasing vulnerability to natural hazards, particularly landslides. Selected for its geographic proximity to Constantine and its availability of low-yield land, the site was planned to accommodate 300,000 residents across 1,500 hectares, in line with national decentralization and balanced development policies. This study adopts a multidisciplinary methodology, including literature review, analysis of urban master plans, field observations, and interviews, to explore the city’s functional evolution. Initially conceived as a residential relocation zone, Ali Mendjeli has undergone a dynamic transformation. By 2020, its population reached 461,885 with over 73,000 housing units. It evolved into a major academic center, hosting two university poles and receiving more than 30,000 students daily surpassing Constantine in student influx. This educational shift has significantly reinforced its regional influence. In parallel, a growing commercial function has emerged, reflected in the development of seven operational malls and nine more in planning or construction. This shift is largely driven by the retail decline in Constantine’s center, prompting traders to relocate. Ritaj Mall, for instance, illustrates this trend with a strong attraction rate of 2.59 and a commercial environment dominated by non-food stores (72.2%). Ali Mendjeli’s transformation from a residential extension to a vibrant academic and commercial hub highlights the importance of functional diversity in forging a city’s identity. These evolving roles not only enhance urban resilience but also strengthen the city’s capacity to serve as a self-sustaining and integrated urban pole within Algeria’s national urban network, raising important questions about its next phase of transformation and future identity.